2014
DOI: 10.1002/2014jf003143
|View full text |Cite
|
Sign up to set email alerts
|

The importance of bed sediment sand content for the structure of a static armor layer in a gravel bed river

Abstract: The surface structure of static armor layers generated from water-worked gravel bed channels was investigated with primary focus on the influence of sand content and flow rate. Flume experiments were conducted in which four sediment mixtures with sand contents between 1% and 38% were armored under one of three different flow rates. First-and second-order statistical analyses were applied to digital elevation models of unarmored, armored, and clustered bed surface areas to identify changes in surface structure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 48 publications
2
42
0
Order By: Relevance
“…If a dynamic system of river beds, other than sand dunes, is employed to examine the relationship between the spectral behavior and the kinetic or geometrical characteristics of the system, the previous explanations can then be tested. The grain size distribution of river beds has been found to have significant influence on the typology and sediment movement of river beds (Parker, 1990;Powell, 1998;Wilcock, 1998;Wilcock and Crowe, 2003;Curran and Wilcock, 2005;Mao et al, 2008;Mao and Surian, 2010;Podolak and Wilcock, 2013;Curran and Waters, 2014). As a consequence, surfaces composed by sediment coarser than sand can be used to investigate the validity of the '−3' spectral law and verify the existing explanations for this law.…”
Section: Introductionmentioning
confidence: 96%
“…If a dynamic system of river beds, other than sand dunes, is employed to examine the relationship between the spectral behavior and the kinetic or geometrical characteristics of the system, the previous explanations can then be tested. The grain size distribution of river beds has been found to have significant influence on the typology and sediment movement of river beds (Parker, 1990;Powell, 1998;Wilcock, 1998;Wilcock and Crowe, 2003;Curran and Wilcock, 2005;Mao et al, 2008;Mao and Surian, 2010;Podolak and Wilcock, 2013;Curran and Waters, 2014). As a consequence, surfaces composed by sediment coarser than sand can be used to investigate the validity of the '−3' spectral law and verify the existing explanations for this law.…”
Section: Introductionmentioning
confidence: 96%
“…The experiments by Dietrich et al (1989) showed that a decrease in the sediment supply rate corresponds to a more efficient armor development. Also, the grain size distribution of the bed material and, in particular, the increase in sand content plays a role in the armoring process by reducing vertical sorting (Marion and Fraccarollo, 1997) or by reducing surface roughness and facilitating the rearrangement of the bed particles (Curran and Waters, 2014). Another aspect is the influence of different flow rates on the development of the armor (Hassan et al, 2006;Guney et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding to these regimes, we define the vertical length scale as the standard deviation of the gridded surface height, z , because the value of structure function, D G2 , in the saturation regime is found to approximately scale as 2 2 z . The complexity and irregularity of the streambeds can be quantified by the Hurst exponent (H x or H y ), which is half the exponent of the power law in the scaling regime (Nikora et al, 1998;Aberle and Nikora, 2006;Curran and Waters, 2014). The complexity and irregularity of the streambeds can be quantified by the Hurst exponent (H x or H y ), which is half the exponent of the power law in the scaling regime (Nikora et al, 1998;Aberle and Nikora, 2006;Curran and Waters, 2014).…”
Section: Surface Roughness Characterizationmentioning
confidence: 99%